Three new species of Freycinetia (Pandanaceae) from Kalimantan, Indonesia - Keim, Ary Prihardhyanto (REINWARDTIA, 2009)
Three new species of Freycinetia (Pandanaceae) from Kalimantan (Indonesian Borneo) are firstly described in this paper namely F. kartawinatae A.P. Keim, F. runcingensis A. P. Keim, and F. subracemosa A.P. Keim.